KONTRIBUSI KELENTUKAN PERGELANGAN TANGAN DAN KOORDINASI MATA-TANGAN DENGAN KEMAMPUAN SERVIS FOREHAND TENIS MEJA PADA SISWA EKSTRAKURIKULER SMK NEGERI 1 PASIR PENYU - Ardianto Ardianto; Zainur Zainur; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract; When they saw the problems in the field, the researchers made observations at the SMK 1 STATE VOCATIONAL SCHOOL, SAND TURTLE water. The problems that arise are: some students are not optimal at doing table tennis service, this is seen in the results of the service ball in which the net is involved, from the field, the level of responsibility so easily dismantled by the opponent and the timing of the bet blows against the ball so that the ball does not go fast. This problem is thought to be due to the lack of connection between wrist flexion and eye-hand coordination of the forehand services performed. The purpose of this study was to determine whether wrist flexion and eye-hand coordination contribute to the ability of the forehand service for table tennis. The population in this study consisted of all students who participated in extracurricular table tennis at SMK Negeri 1 Pasir Penyu, a total of 12 people. The sampling technique in this study is the total sampling technique. This means that the entire population is sampled, so the sample in this study was 12 people. The instruments in this study were the wrist flexion test, the tennis ball catching test and the table tennis advance service test. Data obtained from analysis using product moment correlation. The following conclusions can be drawn based on the results of research described by the author in the previous chapter. Of the obtained wrist flexion results, a relationship with forehand service capacity among out-of-school students of table tennis SMK Negeri 1 Pasir Penyu with a contribution of 38.19%. The results obtained through eye and hand coordination have a relationship with the ability to pre-serve out-of-school table tennis students from SMK Negeri 1 Pasir Turtle with a contribution of 66.59%. There is a joint relationship between wrist flexion and eye and hand coordination on the service capacity of the forehand among out-of-school students of SMK Negeri 1 Pasir Penyu with a contribution of 68.39%.Key Words: wrist speculation, eye and hand coordination, service in advance